The portability of new immigrants' human capital: Language, education and occupational matching - Gustave Goldmann; Arthur Sweetman; Casey Warman (Institute for the Study of Labor (IZA), 2011)
The implications of human capital portability - including interactions between education, language skills and pre- and post-immigration occupational matching - for earnings are explored for new immigrants to Canada. Given the importance of occupation-specific skills, as a precursor we also investigate occupational mobility and observe convergence toward the occupational skill distribution of the domestic population, although four years after landing immigrants remain less likely have a high skilled job. Immigrants who are able to match their source and host country occupations obtain higher earnings. However, surprisingly, neither matching nor language skills have any impact on the return to pre-immigration work experience, which is observed to be statistically significantly negative. Crucially, English language skills are found to have an appreciable direct impact on earnings, and to mediate the return to pre-immigration education but not labour market experience.
urn:nbn:de:101:1-201107283773
Keywords: J24; J61; J62; 330; immigration; human capital portability; occupation; language; education